PERAN LINGKUNGAN SEKOLAH DALAM MENDUKUNG TUMBUH KEMBANG ANAK USIA SEKOLAH - Anita Ulpa; Roza Naulia Rosdianti; Firsty Sofila; Nia Ikhtanova; Adellar Prasetya; Rahmatul Husna; Hafiz Hidayat (STKIP Subang, 2025)
The school environment plays a crucial role in supporting the growth and development of elementary school-aged children. Children at this stage experience rapid physical, cognitive, social, and emotional development that requires a safe, supportive, and stimulating learning environment. This study aims to analyze the role of the school environment in supporting the growth and development of elementary school children through a literature review. The research employed a literature study method by reviewing relevant national and international journal articles, books, and scientific publications related to school environment and child development. Data were collected through systematic searches of academic databases and analyzed using thematic analysis. The results indicate that the school environment—including physical environment, social environment, and learning climate—significantly influences children’s physical growth, motor development, cognitive abilities, social skills, and emotional well-being. A safe, inclusive, and child-friendly school environment fosters optimal development and enhances students’ learning motivation and well-being. This study concludes that creating a supportive school environment is essential for optimizing the holistic growth and development of elementary school children and recommends strengthening school policies oriented toward child-friendly and developmentally appropriate educational practices.